Computational investigation of peptide binding affinity and complex stability of major histocompatibility complex (mhc) - Bunsuz, Asuman (My University, 2018)
ÖZETMAJOR HISTOKOMPATİBİLİTE KOMPLEKSİNİN PEPTİT BAĞLANMA AFİNİTESİNİN VE KOMPLEKS STABİLİTESİNİN HESAPLAMALI ARAŞTIRILMASIMajör Histokompatibilite Kompleks Molekülleri (MHC) antijenik peptitlere bağlanarak ve onları T hücre tanınması için hücre yüzeyinde sunarak adaptif immune cevabın düzenlenmesinde özgün bir rol oynayan heterodimerik hücre yüzey glikoproteinleridir. İnsanlarda MHC molekülleri İnsan Lökosit Antijeni (HLA) olarak adlandırılır. HLA-A2 farklı etnik popülasyonlarda yaygın olarak bulunan HLA-A alelidir. HLA-A*02:01 HLA-A2 alel varyantları arasında en yaygın olan ve HLA-A2 sınırlı sitotoksik T lemfosit cevaplarını çalışmak için çoğunlukla kullanılan alleldir. Son zamanlarda çalışmalar peptit temelli aşıların tasarlanması üzerine odaklanmıştır bu nedenle peptit immunojenitesini etkileyen faktörler detaylı araştırmalar için popüler konu olmuştur. Çeşitli çalışmalar o peptit immunojenitesi için afinite ve stabilitenin iki en önemli parametre olduğunu ileri sürmektedir. Bu yüzden, peptit bağlanma afinitesini ve peptit-MHC kompleks stabilitesini araştırmak için, çeşitli hesaplamalı teknikler kullandık. 12 peptit-HLA-A*02:01 kompleksi için DockTope web sunucusunu kullanarak moleküler doking çalışmaları gerçekleştirdik. Ardından, modellenmiş yapıların 100 ns parallel moleküler dinamik simülasyonlarını OPLS-AA/ L potansiyel enerji fonksiyonunu kullanarak 310 K ve 473 K de gerçekleştirdik. Son aşamada, çiftli aminoasit etkileşim enerjilerini gRINN aracılığıyla hespladık ve bu 12 peptit-HLA-A*02:01 kompleksinin gözlenen stabilite farklılıklarında önemli rol oynayan kritik rezidüleri ortaya çıkardık. Sonuç olarak, hesaplamalı sonuçlarımız peptit immunojenitesi için stabilitenin daha anlamlı parametre olduğunu gösteren deneysel çalışmalarla aynı doğrultudadır.TABLE OF CONTENT PAGEACKNOWLEDGEMENTSiTABLE OF CONTENTiiABSTRACTivÖZETvLIST OF SYMBOLSviLIST OF ABBREVATIONSviiCHAPTER 1 AIM OF THE STUDY13CHAPTER 2 INTRODUCTION152.1Structure of Major Histocompatibility Complex (MHC)152.2HLA peptide binding affinity and stability182.3Molecular Dynamics (MD) Simulations212.3.1Theoretical Background of Molecular Dynamics Simulations222.3.2Molecular Dynamics (MD) Simulations of peptide-HLA Class I Complexes242.4Molecular Docking of HLA Class I Molecules262.4.1DockTope Server28CHAPTER 3 MATERIALS AND METHODS303.1HLA-A*02:01 Structures303.2Molecular Docking of HLA-A*02:01 Structures333.3Preparations of Structures for MD Simulations333.4Analysis of the MD Simulation Trajectories343.4.1Root Mean Square Deviation (RMSD) Calculations343.4.2Root Mean Square Fluctuation (RMSF) calculations353.5Calculation of pairwise amino acid non-bonded interaction energies via gRINN tool35CHAPTER 4 RESULTS AND DISCUSSIONS364.1 Analysis of RMSD profiles364.2 Analysis of RMSF profiles394.3 Analysis of interaction energies using gRINN42CHAPTER 5 CONCLUSION67CHAPTER 6 FUTURE WORK69REFERENCES70AUTOBIOGRAPHY83

ABSTRACTCOMPUTATIONAL INVESTIGATION OF PEPTIDE BINDING AFFINITY AND COMPLEX STABILITY OF MAJOR HISTOCOMPATIBILITY COMPLEX (MHC) Major histocompatibility complex (MHC) molecules are heterodimeric cell surface glycoproteins playing a novel role in the regulation of the adaptive immune response by binding antigenic peptides and presenting them at the cell surface for T cell recognition. In humans, MHC molecules are called as Human Leukocyte Antigens (HLA). HLA-A2 is the most common HLA-A allele in different ethnic populations. Among the HLA-A2 allelic variants, HLA-A*02:01 is the most frequent one and it is commonly used to study HLA-A2-restricted cytotoxic T lymphocyte (CTL) responses. Recently, studies have focused on designing peptide based vaccines; hence the factors affecting the peptide immunogenicity has become a popular subject for detailed studies. Several studies proposed that affinity and stability are the two most significant parameters for peptide immunogenicity. Therefore, in order to investigate the peptide binding affinity and the stability of peptide-MHC complexes, we have employed various computational techniques. We performed molecular docking studies for 12 peptide-HLA-A*02:01 complexes using DockTope web server. Then, we carried out 100 ns parallel molecular dynamics simulations for the docked structures using GROMACS software with the OPLS-AA/ L all-atom force field at 310 K and 473 K. In the final step, we calculated pairwise amino acid non-bonded interaction energies via gRINN tool and revealed the critical residues that play a role in the observed stability differences for these 12 peptide- HLA-A*02:01 complexes. As a result, our computational results are found to be inline with the experimental studies demonstrating that stability is a more significant parameter for peptide immunogenicity and that computational methods can also be used for the future studies in terms of determining stability of a peptide complex. TABLE OF CONTENT PAGEACKNOWLEDGEMENTSiTABLE OF CONTENTiiABSTRACTivÖZETvLIST OF SYMBOLSviLIST OF ABBREVATIONSviiCHAPTER 1 AIM OF THE STUDY13CHAPTER 2 INTRODUCTION152.1Structure of Major Histocompatibility Complex (MHC)152.2HLA peptide binding affinity and stability182.3Molecular Dynamics (MD) Simulations212.3.1Theoretical Background of Molecular Dynamics Simulations222.3.2Molecular Dynamics (MD) Simulations of peptide-HLA Class I Complexes242.4Molecular Docking of HLA Class I Molecules262.4.1DockTope Server28CHAPTER 3 MATERIALS AND METHODS303.1HLA-A*02:01 Structures303.2Molecular Docking of HLA-A*02:01 Structures333.3Preparations of Structures for MD Simulations333.4Analysis of the MD Simulation Trajectories343.4.1Root Mean Square Deviation (RMSD) Calculations343.4.2Root Mean Square Fluctuation (RMSF) calculations353.5Calculation of pairwise amino acid non-bonded interaction energies via gRINN tool35CHAPTER 4 RESULTS AND DISCUSSIONS364.1 Analysis of RMSD profiles364.2 Analysis of RMSF profiles394.3 Analysis of interaction energies using gRINN42CHAPTER 5 CONCLUSION67CHAPTER 6 FUTURE WORK69REFERENCES70AUTOBIOGRAPHY83
Keywords: Bioengineering; Biyomühendislik; HUMAN LEUKOCYTE ANTIGEN(HLA); İNSAN LÖKOSİT ANTİJENİ (HLA); MAJOR HISTOKOMPATİBİLİTE KOMPLEKS (MHC); MOLECULAR DOCKING; MOLECULAR DYNAMIC SIMULATION; MOLEKÜLER DİNAMİK SİMÜLASYONU MAJOR HISTOCOMPATIBILITY COMPLEX (MHC); MOLEKÜLER DOKİNG; PEPTIDE IMMUNOGENICITY; PEPTİT İMMUNOJENİTESİ; STABILITY; STABİLİTE